Expanding hyperspectral imaging applications to the clinical scene: non-invasive, label-free approaches for early diagnostics and precision medicine - Holman, Elizabeth A.; Holman, Derek R.; Rogalla, Stephan (Frontiers in Imaging, 2023)
Non-invasive, label-free hyperspectral imaging technologies are powerful tools that can provide critical insights into the spatiotemporal dynamics of evolving systems. They are already integrated into autonomous adaptive surveillance workflows for precision agriculture, remote sensing, environmental monitoring, and food analysis. However, these technologies are not yet routinely used in medicine. With these technologies applied to the biomedical sciences, we anticipate landmark advances in the physicochemical behavioral refinement of high signal-to-noise probes and in the rapid screening of patient exosome populations. To implement label-free spatiochemical imaging techniques while meeting the practical needs of clinicians, technology, workflow design and development must be tailored to the specific medical field while considering existing visualization modalities. This perspective merges basic, translational, and clinical views of label-free, non-invasive hyperspectral imaging. We explore its potential role in positively impacting cancer-related precision medicine and early diagnostics to support clinically implemented point-of-care technologies.